CMS Phase-2 Inner Tracker Upgrade. Issue 1 (1st November 2022) - Malik, Sudhir; ,
Abstract : The HL-LHC conditions of instantaneous peak luminosity up to 7.5x10 34 cm -2 s -1 and an integrated luminosity of the order of 300 fb -1 /year is expected to result in 1 MeV neutron equivalent fluence of 2.3 x 10 16 neq /cm 2 and a total ionizing dose (TID) of 12 MGy (1.2 Grad) at the center of the CMS Experiment, where its innermost component, the Phase-2 Pixel Detector will be installed. This detector has to survive the above radiation dose, handle hit rates of 3.2 GHz/cm 2 in the layers closest to the beam line, be able to track and separate particles in extremely dense collisions, deal with a pileup of 140-200 collisions per bunch crossing and have a high impact parameter resolution. This translates into a highly granular detector design with thinner sensors and smaller pixels, and a faster and more radiation hard electronics compared to the Phase-1 detector. This contribution reviews the Phase-2 upgrade of the (silicon-based) CMS Inner Tracker focusing on the features of the detector layout and on developments of pixelated devices.